ANALISIS GLOBAL POSITIONING INFRASTRUKTUR DAN JARINGAN SOSIAL MEDIA DALAM BISNIS APLIKASI TRANSPORTASI DARAT ONLINE DI JAKARTA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
Online transportation, the kind of transportation that lately makes people in the world feel eased in terms of transportation. With enough gadgets and applications, we can order a convenient and cheaper transportation. In fact, online transportation is willing to pick us up at home without us having to hitchhike down the highway and wait for the shuttles. Really very pampered with this online transport. However, the success of online transport in this world, not necessarily free of problems. The application of online transport business growth rate dashed quickly with facilities facilities are quite promising. With an online business model using consumer positioning maps can easily see and align to their needs. Transactions via the Internet is better known by the name of e-commerce and e-business. In general e-commerce is defined as any form of trade transactions of goods or services (trade of goods and services) by using electronic media / computer. Essentially, if there is a physical resource or business process that can currently be digitized, then that is where the e-business concept can be implemented.